GENDER IDENTITY CONFUSION AND USE OF PORNOGRAPHY - McTavish, James (Asian Horizons, 2019)
An increasing number of young people are unclear about their gender identity, with more and more males now identifying as females (and vice versa). This modern phenomenon is welcomed by many, although Pope Francis has been an outspoken critic of the so-called “gender ideology.” He describes it as a new form of ideological colonization. The growing gender identity confusion is matched by a concurrent increase in internet pornography. The vision of human sexuality and intimacy now portrayed on screen is often skewed, and sends a confusing message to young people. This author explores the possible connection between increasing internet pornography use and the growing gender identity confusion, especially among young people in an Asian context.